2016
DOI: 10.1017/s0022029916000510
|View full text |Cite
|
Sign up to set email alerts
|

Claw disorders in dairy cattle – an unexpected association between energy metabolism and sole haemorrhages

Abstract: The present study investigated whether changes of energy metabolism post-partum (pp) are associated with claw health. For this purpose, back-fat-thickness (BFT) was measured and blood samples were taken from 146 cows at four examination times. The serum levels of free fatty acids (FFA), ß-hydroxybutyrate (BHB) and glucose were measured. Furthermore, in the first week postpartum (pp) and at 8 weeks pp, a claw trimming was done and the presence and extent of sole haemorrhages (SH) was recorded. Animals with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In a multiyear study of one herd analyzing 79,565 cow-weeks at risk, BCS <2 was associated with greater risk of lameness events (Randall et al, 2015). This association has also been found by other researchers (Espejo et al, 2006;Hoedemaker et al, 2009;Green et al, 2014) and a possible etiology with reduced shock absorbance due to a decreased digital adipose cushion thickness in thin cows is postulated (Bicalho and Oikonomou, 2013;Griffiths et al, 2020) and may lead to increased risk of sole hemorrhages (Wilhelm et al, 2017).…”
Section: The Importance Of Transition Period Adipose Tissue On Disease Risksupporting
confidence: 72%
“…In a multiyear study of one herd analyzing 79,565 cow-weeks at risk, BCS <2 was associated with greater risk of lameness events (Randall et al, 2015). This association has also been found by other researchers (Espejo et al, 2006;Hoedemaker et al, 2009;Green et al, 2014) and a possible etiology with reduced shock absorbance due to a decreased digital adipose cushion thickness in thin cows is postulated (Bicalho and Oikonomou, 2013;Griffiths et al, 2020) and may lead to increased risk of sole hemorrhages (Wilhelm et al, 2017).…”
Section: The Importance Of Transition Period Adipose Tissue On Disease Risksupporting
confidence: 72%
“…This relationship may also exist for lameness, but this has not yet been fully studied (Randall et al 2016). According to Wilhelm et al (2017), the body condition before calving, as represented by backfat thickness and which is associated with the "fat pillow" in the hooves, plays an important role in noninfectious claw disorders. Changes in energy metabolism postpartum are associated with claw health, especially in the first 2 months of lactation.…”
Section: Association Of the Number Of Hd During Lactations And Production And Reproduction Parametersmentioning
confidence: 99%
“…These effects of aging are not fully understood, but could be linked to behavioural changes. Several epidemiological studies have shown that animals with low body condition score (BCS) are at risk to become lame (Espejo et al, 2006;Dippel et al, 2009;Randall et al, 2015;Wilhelm et al, 2017). hypothesize that low BCS is linked with thin digital cushions, and thus impaired shock absorption.…”
Section: Risk Factors For Claw and Locomotion Disordersmentioning
confidence: 99%